(untitled) (Faculty of Education Scientific Journal, 2023)
In the present study, a Schiff base (HL1) derived from the condensation reaction of L-alanine with o-hydroxyacetophenone in 1:1 molar ratio was synthesized. The Schiff base and ethylenediamine compound were used to form three mixed ligand chelates with iron(III), cerium(IV) and thorium(IV) ions. The compounds were characterized using several analytical and spectroscopic tools [IR, electronic, NMR and mass]. The results showed the bonding behavior between the ligands and metal ions. The antimicrobial activities of the ligands and mixed ligand chelates were investigated against Staphylococcus aureus, Serratia marcescens, Acinetobacter baumannii and Candida albicans using the agar disk diffusion method. The results indicated that the antimicrobial activity of the tested compounds exhibited a fairly good inhibitory effect on the pathogenic microbe’s species. In contrast, the L-alanine showed no antimicrobial activity against A.baumannii. Schiff base, L-alanine, o-hydroxy acetophenone , [Fe(L1) (L3)(OH)] .H2O, [Ce(L1) (L3)(SO4)(H2O)].H2O and [Th(L1)(L3)(NO3)2]. 2H2O showed bacteriostatic activity against the highly susceptible species of pathogenic bacteria (S. aureus and S. marcescens) with MIC reached 50 mg/ml. while ethylenediamine suppressed bacterial growth of these species at a concentration of 25 mg/ml.